Linguistics for Everyone: An Introduction - Denham, Kristin E.,d1967-; Lobeck, Anne C (Wadsworth, Cencage Learning, 2013)
LINGUISTICS FOR EVERYONE, 2E, International Edition connects the study of linguistics to the language you use every day. The text is very user-friendly: casual writing style, logical presentation of material, balance of theoretical and practical, entertaining information, and lots of ideas and activities to put what you learn to use right away. The first chapter gives you the basics such as how to define language, new ways to look at grammar, your innate knowledge about language. Later chapters address core linguistics areas in depth (phonetics and phonology, morphology, syntax, and semantics). Many innovative and varied activities help you review and practice the content and apply the knowledge immediately. Special features throughout the book demystify common curiosities about how language works